2011
DOI: 10.1089/omi.2011.0090
|View full text |Cite
|
Sign up to set email alerts
|

Models and Tools for Studying Drought Stress Responses in Peas

Abstract: The pea (Pisum sativum L.) is an important pulse crop but the growing area is limited because of its relatively low yield stability. In many parts of the world the most important abiotic factor limiting the survival and yield of plants is the restricted water supply, and the crop productivity can only be increased by improving drought tolerance. Development of pea cultivars well adapted to dry conditions has been one of the major tasks in breeding programs. Conventional breeding of new cultivars for dry condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Although plants survived both short-term drought/re-watering cycles (Figure 1), stress decreased the accumulation of FW (Figure 2A) and DW, which increased by ca 155 mg, while in control plants this was 260 mg. The results of growth inhibition and biomass accumulation, obtained in the present study, confirm those previously published on the effects of soil drought on pea plants [40][41][42][43]. Water stress inhibited vegetative growth, biomass accumulation, water content and photosynthetic pigments of the pea cultivars evaluated [42].…”
Section: The Effect Of Short-term Soil Drought On Plant Growth and Developmentsupporting
confidence: 91%
See 2 more Smart Citations
“…Although plants survived both short-term drought/re-watering cycles (Figure 1), stress decreased the accumulation of FW (Figure 2A) and DW, which increased by ca 155 mg, while in control plants this was 260 mg. The results of growth inhibition and biomass accumulation, obtained in the present study, confirm those previously published on the effects of soil drought on pea plants [40][41][42][43]. Water stress inhibited vegetative growth, biomass accumulation, water content and photosynthetic pigments of the pea cultivars evaluated [42].…”
Section: The Effect Of Short-term Soil Drought On Plant Growth and Developmentsupporting
confidence: 91%
“…In this laboratory experiment, sensitivity to water stress was cultivar dependent. Field trials of peas also showed cultivar differences in response to soil water deficit [43]. Furthermore, the authors of this study showed that there is a decrease in chlorophyll content and leaf greenness in peas, in response to drought stress.…”
Section: The Effect Of Short-term Soil Drought On Plant Growth and Developmentmentioning
confidence: 50%
See 1 more Smart Citation
“…According to this, diverse chlorophyll fluorescence parameters have been shown to reflect the ability of pea plants to maintain photosynthesis under chilling (4 • C to 10 • C) and genetic variability for some of these parameters has been evidenced Lichtenthaler, 1999, 2006). Reduced photosynthesis, lead to reduction of growth, by mean of fresh and dry weight and leaf area in pea (Magyar-Tabori et al, 2011).…”
Section: Abiotic Stress Responsesmentioning
confidence: 99%
“…Their rich dietary fiber and antioxidant contents and important biomolecules have significant potential in promoting health and preventing chronic diseases ( Devi et al., 2023 ). With global climate change, water scarcity has become the major abiotic factor limiting the survival and output of peas, so screening and breeding new drought-tolerant pea varieties is the key to enhance their yield and quality ( Magyar-Tábori et al., 2011 ). Seed germination rate and germination index can be calculated by examining the germination status of pea seeds, which are key indicators for assessing the vigor of seed germination, reflecting the ability of seeds to germinate in suboptimal environments such as low moisture availability ( Ranal and Santana, 2006 ).…”
Section: Introductionmentioning
confidence: 99%